Age effects on retinal blood flow assessed using spectral-domain optical coherence tomography doppler - Yusof @ Alias, Firdaus; Tayyari, Faryan; Flanagan, John G; Hudson, Christopher (2012)
Purpose: To determine the impact of healthy aging upon total retinal blood flow as derived by Spectral-Domain, Optical Coherence Tomography Doppler SD-OCT. Methods: SD-OCT Doppler blood flow was non-invasively measured using the RTVue system (Optovue Inc., USA). One eye of each of 6 healthy young (mean age 25.7; SD 3.5 years) and 6 healthy elderly (mean age 63.5; SD 1.8 years) subjects was randomly selected for the study and dilated using Mydriacyl 1%. A double circular scanning pattern was employed. A minimum of six separate SD-OCT Doppler measurements (i.e. each separate measurement comprising a superior nasal pupil scan and an inferior nasal pupil scan) were acquired. Total retinal blood flow was calculated, using data from valid scans only, by summing flow from all detectable venules. Results: 117 of 170 images (68.82%) were determined to be valid using the DOCTORC software (Centre for Ophthalmic Optics and Lasers, CA,USA). Mean total retinal blood flow for the young group was 44.96±15.59μl/min, while for the elderly group it was 39.45±13.20 μl/min. Two-sided t-test showed no significant difference between both groups (p=0.52). Linear regression analysis showed no significant correlation between total retinal blood flow and age (r=-0.31, p=0.33). Conclusions: Preliminary data acquired using SD-OCT Doppler shows no significant difference in retinal blood flow between a young and elderly group.